Democracy and public administration - Box, Richard C. (M.E. Sharpe, 2007)
The true measure of the successful practice of public service is its ability to remain faithful to the tenets of democratic society. This text links the practice of public administration to the core concepts of American democracy. It covers the various aspects of public administration in the context of ''delivering democracy'' in public service.